The Chronicle of San Juan de la Peña and the narrative of origins (History Journal «Jerónimo Zurita», 2024)
This paper presents some basic questions about the medieval Chronicle of San Juan de la Peña, a literary work of great historiographical importance for the construction of the royal narrative of the Crown of Aragon. The work is widely known and studied, but there are still some aspects of it that need to be resolved. New interpretative keys and reflections will be given here.